Estudo da interação entre cultivares de mandioca e mosca-branca aleurothrixus aepim (goeldi, 1886) (hemiptera: aleyrodidae) em busca de novas fontes de resistência - Ribeiro, Thyago Fernando Lisboa (2020)
Cassava is one of the main crops in Brazil, having a strong economic influence, for agriculture in general. Despite the high agricultural production, this crop suffers greatly from the incidence of pests, which causes considerable losses. Semiochemicals and the development of resistant plants appear as viable and ecologically correct alternatives to act in the control of these pests. In this work, the objective was to analyze the leaf physiology of ten cassava cultivars, identify the VOCs of the cultivars of this cultivar in control plants and infested with whitefly, evaluate the activity of their VOCs and the chemical pattern (E)-β-ocimene against the insect and identify the soluble metabolites of a resistant cultivar (Ecuador 72) and a susceptible cultivar (BRS Jari) in both treatments. The morphological analysis was performed using SEM, where it was possible to observe a high density of trichomes on the abaxial and adaxial surfaces of the resistant cultivar and different organizations of epicuticular waxes in the cultivars. The VOCs were analyzed using CG/MS, identifying a total of 59 compounds from different classes, such as terpenes, hydrocarbons, alcohols, ketones, and aldehydes, which were submitted to multivariate analyzes where group formations were observed, according to the similarity of the VOCs emitted. The plants of the infested treatment showed a significant decrease in the emission of terpenes compared to plants without infestation. The volatile extracts of the BRS Jari and Equador 72 cultivars did not show any significant difference in the olfactometry bioassays, however, the (E)-β-ocimene standard in the concentration of 250 ng/μL showed a significant difference about hexane, showing a repellent action of this compound in front of the whitefly. 16 soluble metabolites present in the cultivars Equador 72 and BRS Jari were identified in the control and infested treatments, among the discriminant metabolites present in the resistant cultivar, two flavonoids were found in high concentrations, Rutina and Kaempferol-3-O-rutinosidic which are related compounds the resistance of plants to insects, a high level of sugars, sucrose, and glucose was also observed, although there is a significant reduction in sugar levels in both cultivars after infestation.